Thalassemia and assisted reproduction: non-transfusion-dependent thalassemia shows no significant effect on live birth rates after embryo transfer - Fan, Li; Wei, Liuyan; Tang, Ni; Li, Zhetao; Li, Wugao; Nong, Liuying; Li, Jingjing; Huang, Wenjie (Frontiers in Cell and Developmental Biology, 2025)
BackgroundThalassemia is a hereditary blood disorder that can impact fertility due to various factors such as iron overload and endocrine disruption. While the effects of iron overload on fertility outcomes in transfusion-dependent thalassemia (TDT) have been well-documented, there is limited data on how NTDT affects assisted reproductive technology (ART) outcomes. This study aims to assess the fertility and pregnancy outcomes of NTDT patients compared to thalassemia carriers (TC) patients in IVF and frozen embryo transfer (FET) cycles.MethodsThis retrospective cohort study analyzed 6,911 female patients who underwent autologous IVF treatment at a private reproductive center between January 2013 and December 2022. The study included women who were carriers of thalassemia or diagnosed with NTDT. ART outcomes, including oocyte retrieval rate, embryo development (maturation rate, number of fertilized oocytes and blastocyst formation rate), clinical pregnancy rate, live birth rate, and miscarriage rate, were compared between NTDT and TC patients. Propensity score matching (PSM) and multivariable adjustments for potential confounders were applied in the statistical analyses.ResultsNTDT patients had a significantly lower oocyte retrieval rate (0.88 vs. 0.93, p < 0.05) and a longer interval from medication initiation to oocyte retrieval (13.35 days vs. 12.38 days, p < 0.05) compared to TC patients. However, NTDT patients exhibited higher oocyte maturation rates and a greater number of fertilized oocytes. Despite these differences in embryo development metrics, there were no statistically significant differences in clinical pregnancy rates and live birth rates between NTDT and TC patients in both fresh embryo transfer (IVF-ET) and FET cycles (p > 0.05). These findings suggest that while NTDT may affect certain aspects of embryo development, it does not significantly impact overall pregnancy outcomes in ART.ConclusionThis study provides valuable insights into ART outcomes for NTDT patients, showing that, despite challenges in oocyte retrieval, their fertility and pregnancy outcomes are comparable to those of thalassemia carriers. Clinicians should consider individualized treatment plans and provide comprehensive counseling for NTDT patients, focusing on their specific fertility characteristics, to optimize ART outcomes. Further research is needed to explore the underlying mechanisms affecting embryo development in NTDT patients and to confirm these findings in broader populations.